Management of emotional intelligence and administration of non-communicable disease screening for posyandu cadres - Tri Wulandari Kesetyaningsih; Tri Pitara Mahanggoro (Community Empowerment, 2023)
Gamping Kidul Hamlet is growing fast and is an education center area. This condition brings social, economic and unhealthy lifestyle changes so that there is concern that there will be an increase in non-communicable diseases (NCDs). This community service is a continuation of the previous program which has formed groups concerned with healthy lifestyles and training in screening and prevention of NCDs. The training aims to enable health cadres to be able to understand and apply management of emotional intelligence for themselves and others as well as be able to apply the administration of NCDs screening in their respective posyandu. The training was attended by 14 participants. The activity was carried out using the discussion method for emotional intelligence management and practice for screening administrative management. At the end of the training, an assessment of the level of emotional intelligence was carried out and the provision of equipment grants for program implementation. The results of the assessment showed that 57% of cadres had high emotional intelligence, 29% are moderate and 14% are low. Emotional intelligence of non-cadres is 84.62% high and 7.69% moderate and low, respectively. The Mann Whitney test proves that the emotional intelligence of cadres is lower than that of non-cadres.